TU3.1 Effect of COVID-19 on stoma formation rates in elective left sided colorectal cancer resections. (9th August 2022) - ElZanati, Hisham; Zohdy, Mohamed; Samuel, Sajanee; Marimuthu, Kalimuthu
Abstract: Aims: The primary aim of the study was to assess the effect of COVID-19 on rate of stoma formation in elective left sided colorectal cancer resections. Other possible effects of COVID-19 on the management of these patients were explored too. Methods: Retrospective review of elective left sided colorectal cancer resections over a 2 years period. Patients were divided into 2 groups, Pre-COVID (4/2019–3/2020) and Post-COVID (4/2020–3/2021) There were 43 resections in the Pre-COVID group and 21 resections in the post-COVID group Results: Patient demographics were comparable in both groups. There was a 30% reduction in total number of colorectal cancer resections and 50% reduction in left sided resections. There was a 3 fold increase in patients not anastomosed primarily post-COVID (from 20.5% to 61%). There was a 2 fold increase in patients ending up with a stoma including patients undergoing primary anastomosis but with defunctioning stomas(from 38.4% to 72.2%). Procedures completed laparoscopically were more or less comparable in both groups. Conversion rate was slightly higher in the post-COVID group (from 14.3% to 21%). Conclusion: Significant increase in stoma formation in the post COVID group most likely due to guidelines from the royal college early in the pandemic but other possibilities include delay in treatment. More studies are required as the pandemic continues to explore this further and determine whether this was justified and to enable us to adapt to the new normal and assess whether we can return safely to our pre-COVID practice without compromising patient outcomes or adding to their morbidity.